The Association of Coping Strategies with Stress, Anxiety, and Depression, with Mediating Role of Job Satisfaction among Traffic Wardens - Imran, Hina; Haider, Hafeez; Shahzadi, Mafia; Unbrin, Aqila; Ramzan, Zoobia (Pakistan Journal of Humanities and Social Sciences, 2023)
The current study aimed to explore the association of coping strategies with stress, anxiety, and depression with the mediating role of job satisfaction among traffic wardens. Participants were taken from the different cities of Punjab Pakistan, such as Faisalabad (N = 39, 21%), Rawalpindi (N = 38, 20.4%), Multan (N = 36, 19.4%), Lahore (N=38, 20.4%) and Gujranwala (N= 35, 18.8%). The current study sample was comprised of 186 traffic wardens. The sample consisted of married (n= 164, 88.2%) and unmarried (n= 22, 11.8%) of the total population. The participant was between 19 - 50 years (M = 34.78, SD = 4.65). A purposive sampling technique was used to collect the data. The variables were assessed through i.e. Demographic Form, Depression, Anxiety, Stress Scale (DASS-21; Lovibond & Lovibond, 1995), translated version by Aslam (2007), Job Satisfaction Survey (JSS; Spector, 1985) translated version by Abbas and Khanam (2016) and Coping Strategies Questionnaire (CSQ; Kausar & Munir, 2004). The results showed coping is the predictor of stress, anxiety, and depression among traffic wardens, with a strong mediating role of job satisfaction. Further, results showed coping has a strong mediating role in job satisfaction. It is concluded that there is a significant association of coping strategies with stress, anxiety, and depression among traffic wardens with mediating role of job satisfaction.